Dehydration affects cardiovascular nitric oxide synthases and caveolins in growing rats - Netti, Vanina Alejandra (2016)
PURPOSE: During the postnatal stage, cardiovascular nitric oxide (NO) system and caveolins (cav) may be regulated differentially in response to hypovolemic state induced by water restriction. Our aim was to examine the effects of water restriction on NO synthases (NOS) and cav in the atria, ventricle and aorta of growing rats. METHODS: Male Sprague-Dawley rats aged 25 and 50 days were divided into (n = 15): WR: water restriction 3 days; WAL: water ad libitum 3 days. Systolic blood pressure, NOS activity and NOS/cav protein levels were measured. RESULTS: Dehydration induced a larger increase in SBP in WR25 group. Ventricular NOS activity, endothelial NOS (eNOS) and neuronal isoform (nNOS) of WR25 pups were increased, and both cav were decreased. In the WR50 group, NOS activity remained unchanged. In the atria, NOS activity, eNOS and nNOS decreased in WR25 associated with increased cav-1; in the WR50 group, NOS activity was increased without changes in NOS isoforms. In the aorta of WR25, NOS activity and inducible NOS (iNOS) were decreased; NOS activity was unchanged in WR50, despite the decreased levels of eNOS and increased iNOS, cav-1 and cav-3. CONCLUSIONS: NO system adjustments in cardiovascular system under osmotic stress in vivo depend on postnatal age, being eNOS and nNOS, the isoforms that determine NOS activity in cardiac tissue in 25-day-old pups. Changes in cav abundance during hypovolemic state may contribute to age-related NO production.